Preoperative Gastric Volume Assessment in Full-Term Pregnant and Non-Pregnant Females: A Prospective Observational Study - Gopal, Nikila Devarayasamudram; Kamaraj, Rajkumaran; Ponnusamy, Reshma; Ramakrishnan, Lakshmi; Subramani, Mouriya (Faculty of Medicine-Universitas Airlangga, 2025)
Introduction: Perioperative pulmonary aspiration (PA) of gastric contents is a serious anesthetic complication that can lead to significant morbidity and mortality. Obstetric patients, due to substantial anatomical and physiological changes, face a significantly higher risk of PA compared to non-pregnant individuals undergoing planned gynecological or other procedures. Objective: The objective of this study is to compare gastric contents and volume through point-of-care gastric ultrasound (PoCUS) in full-term pregnant women and non-pregnant females scheduled for elective surgeries. Methods: This single-center, prospective, observational study included 140 patients who underwent surgery between March 2022 and July 2023. Quantitative and qualitative measurements of the stomach were performed using PoCUS. Results: The study included 140 patients with a mean age of 25±2.5 years (pregnant, range: 22-31 years) and 29±6 years (non-pregnant, range: 21-30 years), respectively. Patients in the pregnant group are classified as ASA II (70 (100%)), while those in the non-pregnant group (ASA I: 22 (31%); ASA II: 48 (69%)) are mixed. In Perlas, a 3-point grading system was used to classify the antrum based on the presence or absence of clear fluid in the supine position. The majority of the pregnant patients’ antrum levels were reported to contain clear fluid (37 (53%)), while in non-pregnant patients, they were empty (45 (64%)). The average gastric antrum cross-sectional area (302.63±4.87 cm2) and gastric volume (1.85±0.5 mL) were found to be high in pregnant females. Conclusion: PoCUS was proven to be a simple, non-invasive method that can evaluate and offer a more precise bedside measurement of gastric volume, both qualitatively and quantitatively, in patients at risk for PA.